Stop Bullying Counseling as an Effort to Prevent Bullying Behavior that Occurs in Students at Ketabang Seruni Elementary School Surabaya - Fatimah, Nurmawati; Khairul Rizki Purba, Abdul; Fithriyah, Izzatul; Purwaningsih, Sri; Setiawati, Yuani; Khaerunnisa, Siti; Akbar Kurniawan, Mohammad (Politeknik Negeri Jember, 2024)
The phenomenon of bullying is a serious problem for child development in Indonesia. Bullying cases in Indonesia are ranked fifth in Indonesia world in bullying incidents (Jayani, 2019). Violence against students at school is a topic of discussion mainstream in the media. The incidence of bullying is 10-60% of children who receive ridicule, ridicule, expulsion, kicking or pushing at least once a week. Cases of bullying in Children can occur anywhere, anytime and by anyone. This makes this case still high incidence rate (Komisi Perlindungan Anak Indonesia, 2020). If this bullying incident continues for a long time, it will have an impact on the victim of bullying, both physically, psychologically and socially. The bullying case at Ketabang Seruni Elementary School Surabaya is of particular concern to the school principal. During break time, students are often heard making fun of each other, and there are friends who are alone because they are ostracized. As a leading public school in the city of Surabaya, hopes that its students can be a good for other schools by implementing free bullying at schools. The solution offered to solve this problem is to provide education to students at Ketabang Seruni Elementary School Surabaya by providing an explanation first about the purpose of the activity, then giving a questionnaire to the students about various things related to the meaning of bullying, types of bullying, causes of bullying, characteristics of perpetrators and victims of bullying, bad impacts of bullying, prevention of bullying, efforts to handle bullying prevention. Education is provided by providing materials using powerpoint media, leaflets and posters which are pasted on the school walls as a means of reminder for the entire community at school, including students, teachers, employees and parents. The result of this activity is that there is an increase in students' understanding of bullying and good practices are obtained by changing the way students socialize to be better and more polite. Keywords — Mental health; Education; Discrimination; Dignity